Factors affecting profitability of palm oil contract arrangements the case of cooperative and non-cooperative growers of Trento, Agusan del Sur - Castillo, Maynard P.
The influence of trade liberalization in the development of agriculture led to the expansion of other countries in terms of land area and production in order to sustain the global supply of industrial products. With this, the linkages between small farmers (cooperative and non-cooperative growers) and the global economy in terms of producing raw materials such as palm oil to supply the growing demand of the world economy as a whole were observed. This study on contract farming and factors that affect profitability of the starting palm oil industry in Mindanao. The evaluation of profitability of different types of growers (cooperative and non-cooperative) was used to check if the project was gaining or not. Primary data were gathered from 40 respondents belonging to CARBEMPCO and CEMPCO and 2 from the outgrowers that were included in the project. Moreover, key informant interviews included the company's field supervisor and government personnel of the Department of Agriculture in Caraga region. The study mainly involved the Agrarian Reform Beneficiary as members of the cooperatives and compared with the non-cooperative members or the outgrowers. The profitability analysis used NPV,BCR and IRR in order to know the present gains of the farmers. The present results reflected negative gains due to internal and external factors that contribute to the profitability of palm oil. Projections were used to assess the profitability in the long-run and reflected positive gains in the future. Profitability ratios on the hand, were used to assess the percentage growth of profitability per hectare and the components farmers' productivity to evaluate the different nature of expenses. Lastly, contract analysis was used to evaluate if the present conditions are followed.